ANALYSIS OF THE NINETEENTH-CENTURY FEMALE CHARACTERS IN THE MEXICAN NARRATIVE: THE SUBMISSIVE WOMAN IN FRONT OF THE FLIRTATIOUS AND LIBERATED - Ortiz Sánchez, Ma. de Lourdes (2021)
In Mexican literature, women are represented as protagonists, active, determined, free, transgressive and intellectual. She is also submissive, obedient and passive in her function as daughter, wife and mother, who complies with the figure of the angel of the home. In some works the corruption of the character is attributed to carelessness in education, personal circumstances or destiny. It is pertinent to analyze from the literary theory its physical profile, which constitutes an element for its degradation or an instrument of seduction, its moral and psychological portrait to conform a personality inclined toward honest or corrupt life.